Front Cover & TOC Vol 9.1 April 2022 - Sujaya, I Nengah (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022, 2022)
Arc Journal. com. Health is an official electronic journal (e-journal) published by PSSKM (School of Public Health) Medical Faculty, Udayana University. This electronic journal can be accessed through: http://ojs.unud.ac.id/index.php/ach